THE DEVELOPMENT OF A CAUSAL FACTORS MODEL INFLUENCING TO TEACHER SPIRITUAL FOR TEACHER STUDENTS OF RAJABHAT - Tuwila, Wichian; Intarasompun , Wichian (Journal of Yanasangvorn Research Institute Mahamakut Buddhist University, 2024)
This research’s objectives were to study; 1. the level of causal factors that influence to teacher spiritual, 2. the level of teacher spiritual of teacher students, 3. the relationship between the causal factors that influence teacher spiritual, and 4. consistency of the model of causal factors. The sample group was 322 teacher students of Rajabhat University, Rattanakosin Group (Bangkok). Research instrument included questionnaires. The statistics used frequency, percentage, mean, standard deviation, Pearson correlation Coefficient and Path analysis with the LISREL program. The research results were as follows: 1.The level of causal factors that influence teacher spiritual of teacher students overall was at a high level. 2. Teacher's spirituality level of teacher students overall was at a high level. 3.The correlation coefficients between all influential causal factors were positively related to the spiritual of teacher students with statistical significance at the 0.01 level. 4. Structural relationship model of causal factors influencing teacher spiritual of teacher students showed the consistent with empirical data. By personal characteristics Intentions in choosing to pursue the teaching profession, in the educational environment, relationships with teachers, and teacher spiritual of student teachers showed the aspect of being a good role model for students was given the most importance, showed the power in predicting teacher spiritual of teacher about 90.00 percents.